Gender Equality: Women's Involvement in Human Resource Management Practices - Allyana Infante; Didit Darmawan (Journal of Social Science Studies (JOS3), 2022)
Ideally every human being has the same right to do a job. Recruitment or assignment must be given based on one's abilities. In practice there is still discrimination against several parties, including women. In assigning tasks, women are considered less able to work and unable to adapt to the work environment. This causes women to be hampered in a career in the company. Companies need resources that have good competence so that company productivity will increase. Women are also able to give good performance, if given the same opportunity to work. In this case, leadership that gives equal rights to women needs to be done so that women are able to show their competence. Various theories and scientific developments on human resources also emphasize gender equality and science-based applications should pay attention to that as well. The involvement of women in human resource practices really must be based on self-competence and self-competitive advantage.